Hydromagnetic free-convection laminar flow of an elasto-viscous fluid past an infinite plate - Samria N.K.; Reddy M.U.S.; Prasad R.; Gupta H.N. (My University, 2025)
The effect of a transverse magnetic field on unsteady free-convection flow of an electrically conducting elasto-viscous fluid (Walters liquid B') past an impulsively started infinite vertical plate is discussed. The Laplace transform technique is used to obtain the expressions for velocity and shearing stress. The influence of the various parameters, entering in the problem, on the velocity field and shearing stress is extensively discussed. © 1991 Kluwer Academic Publishers.